Development of a Ba–CoCe catalyst for the efficient and stable decomposition of ammonia. Issue 9 (26th March 2021) - Morlanés, Natalia; Sayas, Salvador; Shterk, Genrikh; Katikaneni, Sai P.; Harale, Aadesh; Solami, Bandar; Gascon, Jorge
Abstract : CO x -free hydrogen production; cobalt-based catalysts for ammonia decomposition; cerium–barium promoter in cobalt catalysts. Abstract : Barium-promoted cobalt–cerium catalysts prepared by coprecipitation are efficient and stable at decomposing ammonia. Catalysts with the optimal composition show very similar activity and better stability than benchmark solids containing Ru. Characterization studies reveal that cerium plays a key role as a structural promoter, increasing cobalt dispersion and preventing sintering. These features translate into a very active and stable catalyst. Kinetic analysis shows a decrease in the apparent activation energy upon Ba promotion and a decrease in the negative hydrogen reaction order, highlighting the role of the alkaline earth metal in alleviating the negative effect of hydrogen and reducing the hydrogenation properties of cobalt, which results in further improvement of the catalytic activity.